New Criterion of Classification of Blessing: Factors of Placing of their Production. (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In an economic theory many going is known near classification of blessing, but yet never blessing was classified after the factors of placing of production (РP), id est by the factors of place in that the free appears blessing or produced blessing economic. In the article it is suggested to classify blessing after the factors of placing of their production by taking into account of properties of technologies of production of blessing, resources that are used in these technologies, contaminations that appear at a production, and also blessing. First, general, division of blessing after factors them РP it is expedient to execute by dividing of blessing into those, РP that predetermined by the dominant pair of factors (blessing of block A general division), and those, РP that predetermined by a few pairs of factors (blessing of block B general division). The identical blessing can be mine-out by means of different technologies and to be characterized the specific factors of РP. 4 groups of types of the economic blessing (TEB) of block are set A, at РP that dominant property is: 1) presence of corresponding source of resource (natural or anthropogenic); 2) closenesses of market of sale; 3) minimum cost of production of blessing; 4) safe distance from large settlements. In the article an offer matrix is for classification of TEB of block В
Keywords: блага, факторы размещения производства, классификация благ, ресурсы, технология производства, матрица для классификации.